Seroconverting nonresponder of high-dose intramuscular HBV vaccine with intradermal HBV vaccine: A case report. Issue 46 (November 2017) - Das, Manjusha; Vanar, Vishwas; Martin, Daniel K.; Walayat, Saqib; Patel, Jaymon; Badshah, Maaz B.; Kalva, Nikhil R.; Pisoh, Watcoun-Nchinda; Dhillon, Sonu
Abstract: Introduction: Liver disease is a leading cause of death among human immunodeficiency virus (HIV)-infected patients in the United States. Patients with HIV and hepatitis B virus (HBV) coinfection have accelerated liver disease, higher rates of cirrhosis, and liver cancer, and markedly increased liver-related mortality. The CDC and US Advisory Committee on Immunization Practices recommend hepatitis B vaccination for all HIV-infected individuals. Unfortunately, HIV-infected patients have a worse response rate after standard HBV vaccination. Intradermal (ID) vaccination continues to emerge as an important modality in such difficult to vaccinate individuals and should be considered whenever permissible. Herein, we report a case of a 46-year-old male with HIV who failed to mount an immune response to standard intramuscular vaccine, standard booster dose, and repeat high-dose booster vaccine but subsequently mounted an immune response to the ID vaccine which was sustained at 3 months postvaccination. Conclusion: ID vaccination continues to emerge as an important modality in difficult to vaccinate individuals and should be considered in all applicable cases